Quality management system of Lorma Medical Center, Inc., City of San Fernando, La Union - Calderon, Lady Mae B. (City of San Fernando, La Union : [s.n.], 2017)
The study determined the quality management system of Lorma Medical Center, Ins., along the level of implementation of the employees as a basis for the Validated Enhanced Policies. This study sought to find the level of implementation of quality management system along human resource management, security management, nursing management and patient safety management; the level of satisfaction to quality management system along in-patient and out-patient; and the formulation of the validated enhanced policies to appraise the level of implementation of QMS to Lorma Medical Center, Inc., City of San Fernando, La Union.
Bibliography: pages 100-105.
CHED-La Union
Keywords: Total quality management